2020
DOI: 10.1177/1040638720963132
|View full text |Cite
|
Sign up to set email alerts
|

CD3-CD20–positive nodal lymphoma with cross-lineage rearrangement in a dog

Abstract: A 7-y-old mixed-breed male dog was presented with a history of generalized lymphadenopathy. Fine-needle aspirates of the enlarged peripheral lymph nodes were suggestive of lymphoma. Histologic examination of a retromandibular lymph node was suggestive of high-grade, medium large-cell lymphoma. Immunohistochemistry revealed concurrent expression of CD3 and CD20. The co-localization of the 2 antigens was confirmed by immunofluorescence. PCR for antigen receptor gene rearrangements (PARR) detected clonal rearrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
(15 reference statements)
0
7
1
Order By: Relevance
“…Co-expression of CD3 and CD20 confirmed by immunohistochemistry is rare and has been described in only a few cases of canine T-cell lymphomas, such as cutaneous, intestinal, nodal, and peripheral lymphomas with infiltration of the heart and peripheral nerves [ 9 , 10 , 11 , 20 ]. Double lymphoid labelling has also been described in a cat, but in a B-cell lymphoma with expression of CD3, identified by clonality tests [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-expression of CD3 and CD20 confirmed by immunohistochemistry is rare and has been described in only a few cases of canine T-cell lymphomas, such as cutaneous, intestinal, nodal, and peripheral lymphomas with infiltration of the heart and peripheral nerves [ 9 , 10 , 11 , 20 ]. Double lymphoid labelling has also been described in a cat, but in a B-cell lymphoma with expression of CD3, identified by clonality tests [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…With these methods, it is expected that most neoplastic cells from intestinal lymphoid tumors will express either one of the T- or B-cell markers, but not both. However, there are already some reports of co-expression of CD3 and CD20 in canine lymphomas, including three cases of intestinal T-cell lymphomas associated with type 1 EATL [ 9 , 10 , 11 ]. These findings reinforce the importance of PCR for antigen receptor rearrangement (PARR) for a definitive diagnosis of lymphoid cells in intestinal neoplasms [ 1 , 2 , 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clonality for B/T cell lymphoma is rarely observed; however, some authors have reported a cross-line between T and B lymphocytes, positive for both clones by immunohistochemistry and PCR, the last technique being performed to confirm lymphoid clonality [9]. This is because the test performed using PCR is considered more sensitive for detection.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the test performed using PCR is considered more sensitive for detection. One of the hypotheses raised for this type of lymphoma is that a chromosomal mutation occurs, causing the exchange of phenotypic receptors; that is, a lymphoma starts as B cells, and in contact with exogenous factors, it can undergo changes and express a T phenotype, and clonal detection may occur for techniques, such as immunohistochemistry or both sets of primers by PCR [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…The PCR for antigen receptor rearrangement analysis (PARR) was performed on the remaining specimens of LN aspirate, PB, and BM, according to protocols published previously. 12 Clonal cross-rearrangement of both B-and T-cell receptors (BCR and TCR) was retrieved on all 3 matrices, and peaks were superimposable (Suppl. Fig.…”
mentioning
confidence: 99%